Laparoscopic transperitoneal approach for vesicovaginal repair : The first experience in Hasan Sadikin Hospital - Santoso, Jumadi; Pramod, Sawkar Vijay (Indonesian Journal of Urology, 2015)
Introduction : Obstetric ﬁstula is a severe and debilitating condition occurring throughout the developing world. Although there are no accurate data on the incidence and prevalence of the condition, the majority of vesicovaginal fistulas develop after gynaecologic surgery, with transperitoneal hysterectomy accounting for 90% of cases. Several techniques are available for repairing the fistulas. Transperitoneal  approaches give good results even for difficult posterior located fistulas, but are associated with increased morbidity compared with the transvaginal approach. We performed a laparoscopic repair and omentum interposition. Objective : To report our first experience in transperitoneal laparoscopic repair of vesicovaginal fistula in Hasan Sadikin Hospital. Patient and Method : A 31-year-old female presented with vesicovaginal fistula after sectio caersaeran. After a failed trial of conservative treatment with catheter drainage, a transperitoneal laparoscopic repair was performed. Cystoscopy was performed initially to confirm the fistula location and for bilateral ureteric catheterization. A 4-port technique was performed with the patient in the position with her legs in lithotomy position. Without opening the bladder, the fistula tract was excised with separation of the bladder from the anterior vagina wall. Both the bladder and vagina walls were then closed separately using intracorporeal suturing with an interpositional omentum. Result : Total operative time was 270 min. Normal diet was resumed on day 1, drain was removed on  post operatif day 1 and patient was discharged on the second day  with an indwelling catheter. Good cosmetic result on wound operation  and no leakage under cystogram after 2 weeks. The catheter was removed after 2 weeks. Conclusion : Laparoscopic transperitoneal repair of vesicovaginal fistula  with omentum inteposition  is feasible in  Hasan Sadikin Hospital with good outcomes, short hospital days,  and good cosmetics result. Keywords : Fistula vesico vaginal, laparoscopic.